PRODUCTION POTENTIAL OF EXOTIC CARPS IN COMPOSITE CULTURE UNDER SUB-TEMPERATE CONDITIONS - CHAUHAN, RAMESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The study deals with composite culture of exotic carps. The production potential of Cyprinus carpio communis, Ctenopharyngodon idella and Hypothalmichthys molitrix with stocking ratios of 3 : 2: 1 respectively in semi-intensive composite culture was investigated under sub-temperate agro-ecological conditions of lower Kullu valley. Growth rate of C idella was found maximum followed by H. molitrix and C. carpio. The total biomass production was recorded 51.13 q/ha/yr, which is very encouraging under Subtemperate climatic conditions. However, when considered for all the three species, the growth rate of C. carpio was obtained very low as compared to other species, as 50% of this contributed only 23% to the total gross production. Thus the present study certainly indicated for the change of stocking ratios in favour of fast growing species to get slightly higher yields.